PENGARUH HARGA PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION BRAND LOKAL DIKALANGAN GENERASI Z - Dien Hafifah Mesayu Putri (BIEMA, 2021)
Fashion is popular in every generation and the trend keeps changing so it never dies. Z generation oftenly being the target for fashion brand local. This research is using quanitative method. The populations are Z generation that was born in 1995-2005 who's located in South Jakarta. The sampling method used purposive sampling and a total sample is 75 respondents. Data analysis used descriptive and inferential analysis with Partial Least Square (PLS). The result shows that price has a correlation value of 0.536, the correltion value of promotion is 0.216, and the correlation value of product quality is 0.035. And then, price (X1) and promotion (X2) affects purchase decision (Y) and product quality (X3) doesn't affects purchased decision (Y). Simultaneously, the influence price, promotion, and quality product toward purchase decision is 44% and the remaining is influenced by any other variables.